Entrepreneurial finance : a casebook / Paul A. Gompers, William Sahlman. - Gompers, Paul A (Paul Alan) (Van Nostrand Reinhold, 2002)
This casebook allows readers to gain insight into the real world of entrepreneurial finance while sharpening their analytical skills.